Islamophobia and Counter-Terrorism Policies in Indonesia - Paryanto, Paryanto; Lega, Michael; Rahmadi, Andhi Nur; Herizal, Herizal; Bachtiar, Hasnan (Journal of Governance and Social Policy, 2023)
This research aims to develop the comprehensionof the presence of an Islamophobicoutlook in counter-terrorism measures in Indonesia. Thisoutlook affects both the process of formulating and implementing counter-terrorism policies.This undergoes a process of institutionalization by interpreting terrorism in statutory regulations because it crept through a formal structure whileformulating the policy.By using a qualitative approach, and content and critical analysis, this research investigates three cases of the implementation of the counter-terrorism policies:the screening of Muhammad and Alis names at Soekarno Hatta airport, contradiction in the status of the bomber by Leopard at the Taman Anggrek Mall, and the identification of Siyono as an extreme Islamic activist.We argue that the implementation of counter-terrorism policies encounters accountability issues, especially regarding the emergence of authority abuse and double standards during implementation. It confirms the public perception that the counter-terrorism policy is imbued with hostility towards Islam.